Humanin exerts neuroprotection during cardiac ischemia-reperfusion injury - Sirinart Kumfu (2018)
© 2018 - IOS Press and the authors. All rights reserved. Cardiac ischemia-reperfusion (I/R) injury has been shown to impair brain function. Humanin analogue (HNG) given prior to cardiac ischemia has been shown to attenuate both heart and brain mitochondrial dysfunction caused by cardiac I/R injury. In a clinical setting, patients received medical treatment for acute myocardial infarction either during or after the onset of myocardial ischemia; thus, in this study, we tested the hypothesis that the administration of HNG during cardiac I/R injury has therapeutic potential for brain protection. Thirty-six male Wistar rats were divided into two groups: a cardiac I/R group (n = 30), and a sham group (n = 6). The I/R rats were then divided into five subgroups to receive: 1) vehicle; 2) HNG (84μg/kg); 3) HNG (168 μg/kg); 4) HNG (252 μg/kg) intravenously administered during the cardiac-ischemia; and 5) HNG at 252μg/kg given at the onset of reperfusion. At the end of treatment, brains were removed for determination of blood-brain barrier (BBB) breakdown, oxidative stress, brain mitochondrial function, brain mitochondrial dynamics, p-tau, amyloid-β (Aβ) and apoptosis. HNG at a dose of 168 and 252 μg/kg administered during ischemia, and 252 μg/kg given at the onset of reperfusion effectively attenuated the brain mitochondrial dysfunction, tau hyperphosphorylation and Aβ accumulation, and apoptosis, without reducing BBB breakdown, brain oxidative stress, or mitochondrial dynamics, caused by cardiac I/R injury. In conclusion, humanin exerted neuroprotection during induced cardiac I/R injury via improvement in brain mitochondrial function, and the reduction of Alzheimer's disease pathology and apoptosis.